GBS for Ipomoea trifida: A next generation marker system for sweetpotatoes - Khan, A.; David, M.; Simon, R.; Díaz, F.; Eyzaguirre, R.; Grüneberg, W.J. (2015)
Sweetpotato, the seventh most important food crop worldwide, is valued for combating hunger, malnutrition, and poverty because of its hardy nature, wide adaptability, and tolerance to abiotic stresses. Cultivated sweetpotato is hexaploid (2n = 6x = 90) and due to the complexity of its genome, it is still an orphan in the understanding of its genetics and for making use of its genetic potential. Sequence-based genotyping methods offer new opportunities for sweetpotatoes that could be combined with trait data to identify marker-trait associations and to understand the genetic architecture of traits through QTL and GWAS approaches. A mapping population of Ipomoea trifida, a diploid (2n=2x=30) progenitor of cultivated sweetpotato, was developed at the International Potato Center (CIP) by crossing two lines, M9xM19. This population was genotyped using a genotyping by sequencing (GBS) method where the genomic libraries were constructed using Pst1 as the restriction enzyme after screening several restriction enzymes. The GBS run was done at 96-plex and analyzed using the UNEAK analysis pipeline. HapMap unfiltered SNPs were 5466, VCF SNPs were 7055. Individual depth of VCF SNPs was 15.015 +/- 4.767 and individual missingness was 0.574 +/- .078. GBS offers cost effective and time efficient development of large numbers of SNPs throughout the genome of Ipomea trifida; however, missing data presented a great challenge and their analysis will get more complex in hexaploid sweetpotatoes. The GBS markers identified provide a great resource to detect marker-trait associations for several agro-morphological and storage root traits that segregate in this population.